Peningkatan Kemampuan Lompat Jauh Mahasiswa melalui Permainan Tradisional Berbasis Kearifan Lokal Papua: Peningkatan Kemampuan Lompat Jauh Mahasiswa melalui Permainan Tradisional Berbasis Kearifan Lokal Papua - Abu Bakar; Agus Kurniadi; Ainun Mardiah (Jurnal Porkes, 2026)
The low level of long jump ability, motivation, and student engagement in track and field training is a major problem that requires an innovative solution. This study aims to analyze the effectiveness of the traditional game “Aga,” based on Papuan local wisdom, in improving students’ long jump ability, motivation, and engagement. The study employed a quantitative approach with a pretest-posttest nonequivalent control group quasi-experimental design. The sample consisted of 70 students selected through purposive sampling, comprising 35 students in the experimental group and 35 students in the control group. The instruments included the long jump test, standing broad jump, 30-meter sprint, and observation sheets for motivation and engagement. Data were analyzed using descriptive statistics and ANCOVA. The results showed that the traditional Aga game had a significant effect on improving long jump performance (F = 34.498; p < 0.001; η²p = 0.340), with the experimental group’s improvement (27.01%) being higher than that of the control group (13.64%). The experimental group demonstrated higher motivation (M = 43.67) compared to the control group (M = 34.66), as well as greater activity levels (M = 3.63) compared to the control group (M = 2.58). The conclusion of this study indicates that the traditional Aga game is effective in improving students’ long jump ability, motivation, and activity level, making it a viable alternative for an innovative, context-based athletics learning model.